Effects of Continuous Pollution by Pharmaceutical Micropollutants on the Fouling of a Membrane Bioreactor Treating Domestic Wastewater - Li, Chengcheng; Guigui, Christelle; Cabassud, Corinne (Revue des sciences de l’eau / Journal of Water Science, 2015)
Membrane bioreactors (MBR) are increasingly used for domestic wastewater treatment and reuse and great concerns have been raised in the last decade about some emerging trace pollutants found in aquatic environment, notably pharmaceutical products. As a consequence, the removal of pharmaceutical micropollutants by MBRs has been extensively investigated but there is still a lack of knowledge on the effects of the current presence of pharmaceutical micropollutants in domestic wastewaters on MBR fouling. Among the different pharmaceuticals, it was decided to focus on carbamazepine (CBZ), an anti-epileptic drug, because of its occurrence in domestic wastewaters and persistence in biological processes including MBRs. The chemical analysis of soluble microbial products (SMPs) in the supernatant showed that a continuous introduction of CBZ into a submerged MBR via the feed (about 90 µg/L CBZ in the feed) led to a significant increase in the concentration of proteins whereas no significant change was found for polysaccharides. Size exclusion high performance liquid chromatography (HPLC-SEC) analysis showed that the addition of CBZ induced a significant increase of 10-100 kDa proteins in the supernatant and a slight decrease of 100-1000 kDa proteins. After addition of CBZ a significant increase of transmembrane pressure (TMP) in the MBR was observed, which indicates that the increase of the quantity of 10-100 kDa proteins led to a more severe fouling caused by internal fouling in the biocake that was formed on MBR membrane surface. This study also suggests that 10-100 kDa proteins might play a major role in the TMP jump phenomenon. Moreover it was found that addition of CBZ to the MBR affected the biological activities, as a slight inhibition of the exogenous respiration rate was observed.